Grafting in peri-implant bone defects by in-situ polymer deposition using a 3D pen – in vitro/ ex vivo study (Research, Society and Development, 2022)
Guided Bone Regeneration (GBR) aims to gain or maintain bone volume due to the use of barrier membranes that act for this purpose. This research aims at grafting polymeric filaments into preformed peri-implant bone defects in porcine condyles in vitro/ex vivo, stabilized and grafted with poly(lactic acid) (PLA) and poly(vinyl alcohol) (PVA) polymeric filaments, printed in-situ with a 3D printing pen. Nine porcine condyles received bone defects of 8 mm diameter and 7 mm depth, where occurred the installation of conical implants of 3.5x10 mm. After forming the bone gap region, above the apical bone anchorage, we divided the Poof Bodies (PB) according to the polymeric fill used: G.Control – without filling in the bone gap; G.PLA – with PLA scaffolds and G.PVA – with PVA scaffolds. In another step, the PVA and PLA 3D membranes were compared with the dense polytetrafluoroethylene membrane (PTFE-d). Subsequently, the SkyScan 1172 microtomograph (Bruker-μCT, Kontich, Belgium) analyzed the PB. The analysis corresponding to the total porosity revealed no statistical difference between G.Control (70.44%), G.PLA (59.99%), and G.PVA (57.66%). The closed porosity showed a statistical difference between G.Control (75.509%) and G.PVA (189.19%) and between G.PVA and G.PLA (79,093%). This study demonstrated the possibility of the polymeric filaments of PVA and PLA to fill the bone defects created, revealing an intimate contact on the surface of the implants used. The data suggested a higher porosity of the PVA filament when applied to bone defects or membrane shape.